2018
DOI: 10.3310/hta22550
|View full text |Cite
|
Sign up to set email alerts
|

AVURT: aspirin versus placebo for the treatment of venous leg ulcers – a Phase II pilot randomised controlled trial

Abstract: Background Venous leg ulcers (VLUs) are the most common cause of leg ulceration, affecting 1 in 100 adults. VLUs may take many months to heal (25% fail to heal). Estimated prevalence is between 1% and 3% of the elderly population. Compression is the mainstay of treatment and few additional therapies exist to improve healing. Two previous trials have indicated that low-dose aspirin, as an adjunct to standard care, may improve healing time, but these trials were insufficiently robust. Aspirin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…Phase 2 aspirin vs. placebo for the treatment of venous leg ulcers (AVURT) trial conducted in the UK found no effect on VLU healing with a 300 mg aspirin as an adjunct to compression. The quality of evidence is low due to small sample size related to recruitment barriers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase 2 aspirin vs. placebo for the treatment of venous leg ulcers (AVURT) trial conducted in the UK found no effect on VLU healing with a 300 mg aspirin as an adjunct to compression. The quality of evidence is low due to small sample size related to recruitment barriers.…”
Section: Resultsmentioning
confidence: 99%
“…Aspirin was considered as an adjuvant therapy due to its anti‐inflammatory action . Three studies are in progress or just finalized results on the effect of aspirin on the VLU healing time …”
Section: Introductionmentioning
confidence: 99%
“…Le ulcere varicose rappresentano circa il 70% delle ulcere degli arti inferiori che giungono all'osservazione ambulatoriale; la loro incidenza è dell'1% nella popolazione occidentale, che sale al 3% negli over 65. 2,4,6 Come è noto in circa il 30% dei casi queste lesioni non guariscono entro 6 mesi e l'identificazione dei fattori di rischio appare cruciale ai fini prognostici. 6 Nonostante i recenti progressi in tema di medicazioni avanzate e wound care, le recidive non sono infrequenti e rappresentano un problema per lo specialista ed il paziente; a tutt'oggi le evidenze della Letteratura indicano che il bendaggio elastocompressivo, in particolare ai livelli più alti di compressione, resta fondamentale per il successo del trattamento, 5,7,8 penalizzato spesso però dall'intolleranza del paziente.…”
Section: Discussioneunclassified
“…The results from the primary outcome analysis are also presented. The full results are reported in the HTA report, which is available on NIHR’s online Journal Library (https://www.journalslibrary.nihr.ac.uk/) [14].…”
Section: Introductionmentioning
confidence: 99%